Survei Keterampilan Teknik Dasar Lay Up Dan One Hand Set Shot Pada Siswa Peserta Ekstrakurikuler Bolabasket Sekolah Menengah Atas - Pratama, Kharisma Yudha Eka; Wahyudi, Usman; Fitriady, Gema (Sport Science and Health, 2021)
Abstract: The purpose of this study was to determine the level of basic technical skills of lay up and one hand set shot of basketball extracurricular members at SMAN 1 Turen Malang Regency. This research is a quantitative descriptive study using a survey method. The research subjects were 20 participants. The data analysis technique in this study used the percentage formula. The results showed that the extracurricular participants did the lay up and one hand set shot skills test in the "Enough" category with 13 participants (65.00%). Based on the results of the study it can be concluded that the basic technique skills of lay up and one hand set shot of extracurricular basketball participants at SMAN 1 Turen Malang Regency are included in the "Enough" category.Â Abstrak: Tujuan dari penelitian ini untuk mengetahui tentang tingkat keterampilan teknik dasar lay up dan one hand set shot peserta ekstrakurikuler bolabasket di SMAN 1 Turen Kabupaten Malang. Penelitian ini ialah penelitian deskriptif kuantitatif menggunakan metode survei. Subjek penelitian sebanyak 20 peserta. Teknik analisis data dalam penelitian menggunakan rumus persentase. Hasil penelitian menunjukkan bahwa peserta ekstrakurikuler dalam melakukan tes keterampilan lay up dan one hand set shot pada kategori â€œCukupâ€ dengan 13 peserta (65,00%). Berdasarkan hasil penelitian dapat disimpulkan bahwa kemampuan teknik dasar lay up dan one hand set shot peserta ekstrakurikuler bolabasket SMAN 1 Turen Kabupaten Malang termasuk dalam kategori â€œCukupâ€.